Overweight / obesity and time preference: evidence from a survey among adults in the UK - Morro M.L. Touray; David R. Cohen; Simon Robert Pask Williams; Mohammed Fasihul Alam; Sam Groves; Mirella Longo; Heather Gage (Obesity Facts, 2022)
Introduction: Obesity is a global problem incurring substantial health and economic implications. This has been highlighted by the ongoing COVID-19 pandemic which disproportionately affected obese individuals. Most interventions have concentrated on promotion of physical activities and healthy eating which may involve current sacrifices for future health gains. This study explored the relationship between bodyweight and how individuals state they would trade off immediate income for higher amounts in the future (time-preference) Methods: An online survey was conducted targeting adults aged > 16 years in UK from 1/01/2016 to 31/07/2016. Using paid online adverts, as well as personal and professional networks for distribution of links to the online survey, the questionnaire asked respondents to report socio-economic and demographic information, height and weight and to complete a time-preference exercise. Data were analysed using descriptive statistics; associations were explored between BMI and respondents’ characteristics and time preference using Spearman rank-order correlation and Chi-square tests as appropriate. We adopted STROBE guidelines for the reporting of the study. Results: A total of 561 responses were analysed (female = 293, males = 268). The relationship between time-preference and overweight/obese, using BMI as the measure, is highly significant (Chi-Square = 95.92: P < 0001). Individuals of normal weight have low time preference and more likely to invest in activities in a bid to reap future health benefits. There are also significant relationships between BMI and employment status (Chi-Square = 37.03; P < 0.001), physical activities (P < 0.0001), income levels (Chi-Square = 6.68; P < 0.035), family orientation i.e. with or without children (Chi-Square = 12.88; P < 0.012) and ethnicity (Chi-Square = 18.31; P < 0.001). These imply that individuals in employment and with children in their families are less likely to be overweight or obese compared to those who do not. People from black backgrounds are also more likely to be overweight or obese and have higher time-preference compared to people from white backgrounds. Discussions/Conclusions: People’s preventive behaviours today can be predicted by their time preference and this understanding could be vital in improving population’s uptake and maintenance of overweight and obesity prevention actions. People who have low time-preference are more likely to invest time and resources in physical activities and healthy lifestyles to reap future health benefits hence value utilities-in-anticipation.